2016
DOI: 10.1038/srep31732
|View full text |Cite
|
Sign up to set email alerts
|

Relative vascular permeability and vascularity across different regions of the rat nasal mucosa: implications for nasal physiology and drug delivery

Abstract: Intranasal administration provides a non-invasive drug delivery route that has been proposed to target macromolecules either to the brain via direct extracellular cranial nerve-associated pathways or to the periphery via absorption into the systemic circulation. Delivering drugs to nasal regions that have lower vascular density and/or permeability may allow more drug to access the extracellular cranial nerve-associated pathways and therefore favor delivery to the brain. However, relative vascular permeabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…The fluorescent intensity recovery was on the order of tens of seconds in MAP scaffolds, resulting in a calculated diffusivity for 70 kDa dextran ≈50% of that in PBS, while no diffusion was detected into the hydrogel particles in the same timeframe. Given the relatively large hydrodynamic diameter of 70 kDa dextran that is comparable to the nanoscale pores in the gel mesh network, steric hindrance severely limits diffusion within nanoporous hydrogels . In fact, the observation of diffusion in macroscale gels revealed that the diffusivity was 50‐fold lower than that in PBS (0.42 µm 2 s −1 ), in agreement with previous reports .…”
supporting
confidence: 91%
“…The fluorescent intensity recovery was on the order of tens of seconds in MAP scaffolds, resulting in a calculated diffusivity for 70 kDa dextran ≈50% of that in PBS, while no diffusion was detected into the hydrogel particles in the same timeframe. Given the relatively large hydrodynamic diameter of 70 kDa dextran that is comparable to the nanoscale pores in the gel mesh network, steric hindrance severely limits diffusion within nanoporous hydrogels . In fact, the observation of diffusion in macroscale gels revealed that the diffusivity was 50‐fold lower than that in PBS (0.42 µm 2 s −1 ), in agreement with previous reports .…”
supporting
confidence: 91%
“…deep cervical) (Kumar et al . ). Antibody signal was also evident in proximity to several cranial and spinal nerves, some of which appeared to be in the ensheathing dura, possibly associated with dural lymphatics (Aspelund et al .…”
Section: Discussionmentioning
confidence: 97%
“…The anatomic structures of the nasal cavity as well as the physiological and pharmacokinetic mechanisms of the IN administration of drugs might provide an explanation for the effectiveness of IN‐MDZ. The nasal (sub)mucosa provides a large, highly vascular absorptive surface adjacent to the brain and offers a direct pathway for drug absorption into the bloodstream, avoiding the first‐pass hepatic metabolism . This is advantageous for benzodiazepines that need to rapidly accumulate in the brain during emergency management of seizures, but have a relatively short latency of action and undergo extensive hepatic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…MDZ is absorbed by the (sub)mucosal nasal vessels and enters the central nervous system by crossing the blood‐brain barrier, with a rapid clinical effect . In addition, based on laboratory animal and human studies, some drugs, including benzodiazepines, might be able to reach the brain directly via the olfactory and trigeminal neural pathways . The latter might be quite advantageous for refractory cases, where there is inadequate penetration of AEDs across the BBB due to overexpression of drug vascular transporters such as P‐glycoprotein .…”
Section: Discussionmentioning
confidence: 99%